Photocatalytic degradation of methyl red dye - Mahmoud, M.A.; Poncheri, A.; Badr, Y.; Abd El Wahed, M.G. (South African Journal of Science, 2010)
Silica nanoparticles (SiO2 NPs) are active in the photocatalytic degradation of methyl red dye (MR). Si2 NPs and Si2 NPs that have been doped with either silver (Ag NPs) and/or gold nanoparticles (Au NPs) were prepared. The particle size and morphology of the catalysts were assessed by transmission electron microscopy (TEM) imaging. The rate of photocatalytic degradation of MR was found to increase from SiO2 NPs, SiO2 NPs coated with both Au NPs and Ag NPs, SiO2 NPs coated with Ag NPs, SiO2 NPs coated with Au NPs, Ag+-doped SiO2 NPs to Au3+-doped SiO2 NPs.